Identifying well‐being profiles and resilience characteristics in ex‐members of fundamentalist Christian faith communities. (11th May 2022) - Thoma, Myriam V.; Rohner, Shauna L.; Heim, Eva; Hermann, Rahel M.; Roos, Melanie; Evangelista, Keegan W. M.; Nater, Urs M.; Höltge, Jan
Abstract: There is a lack of empirical research on the heterogeneity in well‐being of individuals who disaffiliated (i.e., left or were expelled) from an exclusionary and demanding faith community. Thus, little quantitative knowledge exists on factors related to resilience in these individuals. Therefore, the study aims were twofold: (1) to identify profiles of well‐being in ex‐members; and (2) to examine the characteristics of the identified profiles. A cross‐sectional online survey assessed ex‐members of various fundamentalist Christian faith communities. Latent profile analysis identified latent heterogeneity within the sample. Well‐being profile indicators included perceived stress, psychopathological symptoms, affect, and satisfaction with life. Profile‐related characteristics included socio‐demographics (i.e., gender, age), membership (i.e., reason for joining, duration, extent of involvement, reasons for exit, social support during exit, and time since the exit), and resilience‐supporting resources (i.e., social support, self‐esteem, sense of coherence, personality, socio‐economic status). In the final sample ( N  = 622, Mage  = 41.34 years; 65.60% female), four distinct profiles were identified: resilient (25.70%), normative (36.40%), vulnerable (27.20%), and adverse (10.70%). The resilient profile was characterised by higher age, lower reporting of abuse or maltreatment as exit reason, and highest levels of resilience‐supporting resources. Ex‐members of fundamentalist Christian faith communities differ substantially in their well‐being. Membership aspects were only weakly related to current well‐being, with the exception of the exit reason of abuse or maltreatment. This study provided novel quantitative insights into the well‐being profiles of individuals who disaffiliated from a fundamentalist Christian faith community in German‐speaking countries.